Diagnostic Stewardship in Times of COVID-19 Pandemic - Singhal, Lipika; Kour, Ivneet; Gupta, Varsha (Infectious Disorders - Drug Targets, 2022)
A cluster of unknown acute pneumonia cases by a novel coronavirus signaled an outbreak in Wuhan province of China in December 2019. The World Health Organization (WHO) initially declared COVID-19 as the global public health emergency on 30th January 2020 and subsequently a pandemic on March 11, 2020. It was also stated that the spread of COVID-19 may be interrupted by early detection, isolation, prompt treatment, and the implementation of a robust system to trace contacts. Testing is a key strategy and the role of Diagnostic Stewardship (DS) is essential to allocate and engage the present as well as new testing resources strategically, effectively, efficiently, and safely. Thus, diagnostic stewardship aims to select the right test for the right patient, at the right time to generate accurate, clinically relevant results which will optimally influence better clinical care outcomes and will conserve the available health care resources.
Keywords: COVID-19